All Days 2004
DOI: 10.2118/88566-ms
|View full text |Cite
|
Sign up to set email alerts
|

Subsea Leaks Cured with Pressure-Activated Sealant

Abstract: The paper describes the use of a pressure activated sealant technology to cure leaks in subsea wellbore equipment and control systems. The benefit of this technology is that use of an injectable pressure activated sealant to cure leaks provides a safe, cost-effective alternative to conventional well interventions. The paper outlines the capabilities of the pressure-activated sealants, the procedures used and the results of the sealant operations including case histories. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The addition of rigid particles can cause the surface area to leak area ratio to increase by means of a bridging block in the leak path. As Rusch et al [20] have reported, for a pressure-activated sealant, the higher the surface area to leak area ratio, the more likely it is that the leak is sealed.…”
Section: Comparison Of the Seal Pressures Of Sealants I And Iimentioning
confidence: 97%
“…The addition of rigid particles can cause the surface area to leak area ratio to increase by means of a bridging block in the leak path. As Rusch et al [20] have reported, for a pressure-activated sealant, the higher the surface area to leak area ratio, the more likely it is that the leak is sealed.…”
Section: Comparison Of the Seal Pressures Of Sealants I And Iimentioning
confidence: 97%